Very first real-world data on zongertinib use in non-small cell lung cancer patients with HER2 mutations: A brief report - Oliver Illini; Anna Sophie Lang-Stöberl; Hannah Fabikan; Christoph Weinlinger; Arschang Valipour; Maximilian J. Hochmair (Cancer Treatment and Research Communications)
Introduction: Treatment options for HER2-mutant patients with non-small cell lung cancer (NSCLC) are limited. New agents, including zongertinib, a HER2-selective tyrosine kinase inhibitor (TKI), are being investigated in clinical trials. However, published clinical data on the efficacy and safety of zongertinib are limited to data from a single phase I trial including only 36 patients with NSCLC. Methods: We report real-world data on six consecutive patients with HER2-mutant NSCLC who received zongertinib through a named patient use program between December 2023 and June 2024. Radiological response evaluation and blood testing were routinely performed every two to three months, and adverse events were graded according to the Common Terminology Criteria for Adverse Events (CTCAE) version 5. Results: All patients were diagnosed with a metastatic adenocarcinoma, had previously progressed on at least one line of chemotherapy and had been previously treated with trastuzumab-deruxtecan (two had to stop treatment because of pneumonitis). Three patients (50%) presented with an Eastern Cooperative Oncology Group (ECOG) performance status of ≥2. A clinical and radiological benefit was achieved in all patients (complete response (1), partial response (4), and stable disease (1)). In one patient with brain metastases, a complete response was achieved. Treatment with zongertinib is ongoing in all patients. Adverse events were reported in one patient (elevated blood pressure (grade 1). Conclusion: Zongertinib may be an effective and well-tolerated treatment option for HER2-mutant NSCLC patients even if they are heavily pretreated, have a reduced performance status or have a history of pneumonitis and brain metastases.